Concurrent Extraction and Analysis of Atmospheric Particulate Matter-bound PBDEs, PAHs, Nitrated PAHs, and OPEs - Hsin-Chieh Kung; Bo-Wun Huang; Chien-Er Huang; Nicholas Kiprotich Cheruiyot; Guo-Ping Chang-Chien (Aerosol and Air Quality Research)
Abstract This study aimed to develop and validate a robust method for the simultaneous extraction of polybrominated diphenyl ethers (PBDEs), polycyclic aromatic hydrocarbons (PAHs), nitrated PAHs (N-PAHs), and organophosphate esters (OPEs) bound to atmospheric particulate matter. These compounds are widely distributed pollutants known to have detrimental effects on both human health and the environment. The concurrent microwave extraction took a total of 40 minutes and utilized n-hexane:acetone:dichloromethane (2:2:1 v/v). After a series of cleanup and fractionation steps involving silica gel and alumina columns, PBDEs were analyzed using high-resolution gas chromatography-high-resolution mass spectrometry (HRGC-HRMS), while PAHs, N-PAHs, and OPEs were analyzed using GC-MS/MS. The detected values of the SRM samples (n = 4) were all within 30%, except for 3 N-PAH congeners. The recovery rates for the spiked concentrations (n = 5) were 82.2% ± 8.7%–122% ± 4.4% for PBDEs, 84.2% ± 9.9%–115% ± 17.4% for PAHs, 83.2% ± 2.2%–111% ± 2.5% for N-PAHs, and 93.9% ± 5.3%–111% ± 10.7% for OPEs. These results support the robustness and reliability of the method. The developed method was then applied to real atmospheric PM samples collected from five locations in and around an industrial park in Taiwan during the winter months. Atmospheric PM concentrations ranged from 39.1 to 68.9 µg m−3, with PM-bound OPEs having the highest concentrations (432–2815 pg m−3), followed by PAHs (503–1774 pg m−3), N-PAHs (39.1–277 pg m−3), and PBDEs (5.07–13.6 pg m−3). This method provides a reliable and fast approach to extracting and analyzing multiple compounds from a single atmospheric PM sample. The research contributes significantly to the ongoing efforts to address the critical issue of air pollution.